Answer:
(2, –1)
Explanation:
Substitution Method
2x – y = 5 and 4x + y = 7 are two given equation
Step 1:
Name the Equation
2x – y = 5 ...(1)
4x + y = 7 ...(2)
Step 2:
From equation (1) we get,
2x = y + 5
x = y + 5/2
Step 3:
Substitute the value of x in equation (2)
i.e.,
4(y + 5/2) + y = 7
2(y + 5) + y = 7
2y + 10 + y = 7
3y = 7 - 10
3y = -3
y = -3/3
y = -1
Step 4:
Now, Substitute the value of y in equation (1)
i.e.,
2x – (-1) = 5
2x + 1 = 5
2x = 5 - 4
2x = 4
x = 4/2
x = 2
VERIFICATION:
2(2) – (-1) = 5 i.e., 4 + 1 = 5
4(2) + (-1) = 7 i.e., 8 - 1 = 7